FORMATION OF LOCAL STUDY KNOWLEDGE IN PRIMARY SCHOOL STUDENTS IN THE PROCESS OF GEOGRAPHICAL COURSES - O.R. Lykhovyd (Academy of Cognitive and Natural Sciences, 2010)
The selectin and heterolevels aim formation criteria, forms, in the process of secondary school's local lor, history, and economy work has been worked out have been theoretically defined.